Energy demand and fuel substitution model for urban domestic sector (for electricity planning) the case of Nepal - Rokaya, Kali Bahadur
The Domestic Sector is the major consumer of energy in most developing countries which is also true for many developed countries. Household cooking, which is a very vital and essential end use activity in domestic sector, consumes a major portion of the total energy consumed in this sector. The potential for fuel substitution is also very high for household cooking energy use in domestic sector, specially in urban areas where commercial energy has usually a major share in the total energy consumption. In this study, an analytical model has been developed for energy demand projections and fuel substitution studies for urban domestic sector. The model can be used to update the electric load forecast and consequently the electricity generation expansion plan. The model has been applied to make energy demand projections and fuel substitution studies for urban household cooking in Nepal. The results reveal that the potential for substituting kerosene oil with electricity in urban cooking is very high in Nepal. The change in the electric load forecast for Integrated Nepal power system due to kerosene oil substitution is very significant. The availability of vast hydropower potential makes this substitution possible. The total cost of supplying energy for urban household cooking in Nepal has been calculated for the different scenarios considered. The economic viability of substitution of imported kerosene oil with indigenous hydroelectricity depends on the price of kerosene oil vis-a-vis the cost of developing hydroelectricity.